2018
DOI: 10.1016/j.jdermsci.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A familial case of nail patella syndrome with a heterozygous in-frame indel mutation in the LIM domain of LMX1B

Abstract: Nail patella syndrome is a autosomal dominant disorder caused by a genetic alteration in LMX1B. We identified a novel heterozygous in-frame indel mutation of LMX1B in a family of Nail patella syndrome. Impaired transcriptional activity but not dominant negative effect of mutant LMX1B were revealed using a transcriptional reporter assay, indicating that the mutation caused nail patella syndrome in this family via haploinsufficiency of the transcriptional activity of LMX1B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Intriguingly, sequencing of the shortened PCR products revealed the same splice variant with deletion of exon 2, leading to a frameshift and a downstream premature termination codon (p.Asp49Serfs*17). Our data confirm that NPS is caused by haploinsufficiency of LMX1B as previously reported (27).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Intriguingly, sequencing of the shortened PCR products revealed the same splice variant with deletion of exon 2, leading to a frameshift and a downstream premature termination codon (p.Asp49Serfs*17). Our data confirm that NPS is caused by haploinsufficiency of LMX1B as previously reported (27).…”
Section: Discussionsupporting
confidence: 92%
“…Genetic analysis of NPS has so far determined that haploinsufficiency of LMX1B leads to the clinical manifesta-tion of NPS (27). In this study, we evaluated 2 families with NPS.…”
Section: Discussionmentioning
confidence: 99%
“…Most LIMX1B mutations affect the LIM domains or the homeodomain by altering amino acids that are essential for the binding of zinc or amino acids essential for DNA binding, respectively. Functional studies of a few LMX1B mutations have shown reduced transcriptional activity and decreased DNA-binding ability, resulting in the partial or complete loss of LMX1B function (6,15,22). These and other results suggest that the main pathogenic USA) following the manufacturer's instructions.…”
Section: Mutation Analysismentioning
confidence: 83%
“…NPS is caused by loss‐of‐function mutations in the LMX1B gene, which is expressed in several different tissues and implicated in the clinical phenotype (Dreyer et al., 1998; McIntoshI et al., 1998; Vollrath et al., 1998). The LMX1B gene variants may reduce transcriptional activity and lose the ability to bind DNA (Mukai et al., 2018; Sato et al., 2005). The open reading frame of LMX1B encodes 395 amino acids and contains two N‐terminal zinc‐binding LIM domains, one homeodomain, and a C‐terminal glutamine‐rich domain (Dreyer et al., 2000).…”
Section: Discussionmentioning
confidence: 99%